(untitled) - APFIC (Rome, 1997)
This publication contains a summary report of the tenth session of the APFIC Working Party on Fish Technology and Marketing held in Colombo, Sri Lanka, from 4 to 7 June 1996. It is supplemented by the 46 papaers presented and discussed at the session. The proceedings are divided into five sections. The first section contains papers on public health and fish microbiolgy; the second on the quality and storage of fish and fishy products; the third covers the subject of fish lipids and the fourth product development, particularly from low-valued species. The final section contains five papers of general interest.
Keywords: fisheries